ALA10, a Phospholipid Flippase, Controls FAD2/FAD3 Desaturation of Phosphatidylcholine in the ER and Affects Chloroplast Lipid Composition in Arabidopsis thaliana . Issue 3 (30th November 2015) - Botella, César; Sautron, Emeline; Boudiere, Laurence; Michaud, Morgane; Dubots, Emmanuelle; Yamaryo-Botté, Yoshiki; Albrieux, Catherine; Marechal, Eric; Block, Maryse A.; Jouhet, Juliette
Abstract : The ALA10 phospholipid flippase reduces phosphatidylcholine desaturation and stimulates galactolipid-tophosphatidylcholine ratio in photosynthetic tissues. Abstract: The biogenesis of photosynthetic membranes relies on galactoglycerolipids, which are synthesized via pathways that are dispatched over several cell compartments. This membrane biogenesis requires both trafficking of lipid intermediates and a tight homeostatic regulation. In this work, we address the role of ALA10 (for aminophospholipid ATPase), a P4 -type ATPase, in a process counteracting the monogalactosyldiacylglycerol (MGDG ) shortage in Arabidopsis ( Arabidopsis thaliana ) leaves. ALA10 can interact with protein partners, ALIS1 (for ALA-interacting subunit1) or ALIS5, leading to differential endomembrane localizations of the interacting proteins, close to the plasma membrane with ALIS1 or to chloroplasts with ALIS5. ALA10 interacts also with FATTY ACID DESATURASE2 (FAD2), and modification of ALA10 expression affects phosphatidylcholine (PC ) fatty acyl desaturation by disturbing the balance between FAD2 and FAD3 activities. Modulation of ALA10 expression downstream impacts the fatty acyl composition of chloroplast PC . ALA10 expression also enhances leaf growth and improves the MGDG -PC ratio, possibly through MGDG SYNTHASE1 (MGD1) activation by phosphatidic acid. The positive effect of ALA10 on leaf development is significant in conditions such as upon treatment of plants with Galvestine-1, an inhibitor of MGDG synthases, or when plants are grown at chilling temperature.